Concomitant upregulation of matrix metalloproteinase-2 in lesions and circulating plasma of oral lichen planus - Lo-Lin Tsai; Shun-Fa Yang; Chung-Hung Tsai; Ming-Yung Chou; Yu-Chao Chang (Elsevier, 2009)
Oral lichen planus (OLP) is a chronic inflammatory disorder characterized by a T cell-mediated immune response against epithelial cells. Matrix metalloproteinases (MMPs) are an important group of zinc enzymes and are thought to play an important role in the degradation of components of the extracellular matrix. The aim of this study was to assess the expression of MMP-2 and MMP-9 in both tissue specimens and circulating plasma. Materials and methods: Twelve cases of OLP were collected. In addition, six cases with chronic inflammation and six normal subjects were also recruited. Oral tissue specimens were collected for measurement of MMPs by immunohistochemistry, and sera prepared from peripheral blood were used for gelatin zymography to determine MMP levels in plasma. Results: The level of MMP-2 in patients with OLP was significantly higher than that in the other two groups, both in tissues and sera (P < 0.0001). However, there was no difference in the expression of MMP-9 among these groups. Conclusion: MMP-2 overexpression in OLP is consistent with its upregulation in peripheral serum. This result also indicates that MMP-2 might play a role in the pathogenesis of OLP.